SIMULTANEOUS COCRYSTALLIZATION AND MICRONIZATION OF PARACETAMOL-DIPICOLINIC ACID BY SUPERCRITICAL ANTISOLVENT (SAS) - Hiendrawan, Stevanus
Paracetamol (PCA) is the widely used analgesic and antipyretic drug. In the market, PCA exist as polymorph form I which have poor tabletability. The aim of this study was to improve the tabletability of PCA by using cocrystallization method with dipicolinic acid (DPA) and to evaluate the influence of cocrystal preparation process in the physicochemical propefties of PCA-DPA cocrystal. PCA-DPA cocwstal were prepared using two different process namely rapid solvent evaporation and supercritical antisolvent (SAS). The cocystals were further characterized by powder X-ray diffraction (PXRD), thermal analysis (DSC, and TGA), cold contact method, microscopy analysis (polarized microscopy, and SEM), fomier transform infrared spectroscopy (FTIR), particle size distributions analysis. Flowability, compressibility, dissolution rate, and solubility study of cocrystals were evaluated in com arison to PCA. Distinct PXRD patterns from starting components indicated the formation of new crystalline phase. PXRD analysis showed that products obtained from each method have identical spectra. DSC themograms of PCA-DPA-RE and PCADPA-SAS cocrystal showed a sharp melting endotherm at 193.57 oc dan 194.13 oc which were different from the starting components. FTIR analysis provided clues about the fonnation of amide-carboxylic acid heterosynthon between PCA and DPA. Cocrystal produced by SAS have smaller average particle size than those produced by rapid solvent evaporation process as shown from particle size analysis. Tabletability study revealed superior tableting performance of both cocrystals compare to PCA. PCA-DPA-SAS and PCA-DPA-RE cocrystal show significant enhancement in the dissolution rate approximately 2.45 and 1.72 times compare to PCA alone.